2020
DOI: 10.1039/d0cp00630k
|View full text |Cite
|
Sign up to set email alerts
|

Non network-former cations in oxide glasses spotted by Raman scattering

Abstract: The depolarized Raman spectra can be used as a probe to reveal the presence of non-network formers in oxide glasses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For silicate-based glasses, many attempts of correlation with physical parameters are proposed in the literature for the origins of the BP. Starting from systematic studies of the effect of ionic radius, 21 field strength, 22 and mass 23 of the cations on the BP, studies were extended to cover also the effect of the degree of polymerization as demonstrated by Richet. 24 Besides the atomic properties and the role of oxides, other physical properties such as the effect of fictive temperature of the glass, 25 the fragility index of the predecessor liquid 26 and elastic properties 27 were also reported.…”
Section: Introductionmentioning
confidence: 99%
“…For silicate-based glasses, many attempts of correlation with physical parameters are proposed in the literature for the origins of the BP. Starting from systematic studies of the effect of ionic radius, 21 field strength, 22 and mass 23 of the cations on the BP, studies were extended to cover also the effect of the degree of polymerization as demonstrated by Richet. 24 Besides the atomic properties and the role of oxides, other physical properties such as the effect of fictive temperature of the glass, 25 the fragility index of the predecessor liquid 26 and elastic properties 27 were also reported.…”
Section: Introductionmentioning
confidence: 99%